Gestão de portfólio de produtos em pequenas empresas de base tecnológica - Leoni, Juliene Navas [UNESP]; Jugend, Daniel [UNESP]; Silva, Mila Gibran [UNESP]; Salgado, Manoel Henrique [UNESP]; Silva, Sergio Luiz da (My University, 2014)
The product portfólio management is considered relevant activity to the proper performance of the product development process. This paper aims to present the main methods of management that technology-based small businesses adopt for decision-making in product portfolio. This survey, which collected data on 31 companies was conducted. It was observed that although firms adopt market research and mapping methods and financial methods and for this decision-making, most of them based on the informal deliberations of senior management. Unable to understand the business relationships between the presence of ISO 9001 certification with greater formalization for decision making in product portfolio.

A gestão de portfólio de produtos é considerada atividade relevante para o bom desempenho do processo de desenvolvimento de produtos. Este artigo tem o objetivo de apresentar os principais métodos de gestão que pequenas empresas de base tecnológicas adotam para a tomada de decisão em portfólio de produtos. Foi realizada uma pesquisa tipo survey, a qual coletou dados em 31 empresas. Observou-se que apesar de parte das empresas adotarem a pesquisa de mercado e os métodos de mapeamento e financeiro para esta tomada de decisão, a maioria delas baseia-se nas deliberações informais da alta administração. Não foi possível perceber nas empresas relações entre a presença da certificação ISO 9001 com a maior formalização para a tomada de decisão em portfólio de produtos.
Product portfolio management in small high-tech companies
Keywords: Product portfolio management; Methods for decision making; High-tech companies; Gestão de portfólio de produtos; Métodos para a tomada de decisão; Empresas de base tecnológica